A Comparative Proteome Analysis of Escherichia coli ΔrelA Mutant Cells - Carneiro, Sónia; Villas-Bôas, Silas; Ferreira, Eugénio C.; Rocha, Isabel (Frontiers in Bioengineering and Biotechnology, 2016)
The bacterial RelA-dependent stringent response exerts a strong influence over a wide variety of processes. In this work, the impact of the relA gene mutation in E. coli cells was evaluated by a quantitative proteomics analysis, employing stable-isotope labelling and high resolution mass spectrometry. Chemostat cultures of E. coli W3110 and ∆relA mutant strains were performed at two dilution rates (0.1 and 0.2 h-1) to assess the influence of the relA gene mutation in steady-state protein levels. A total of 121 proteins showed significant alterations in their abundance when comparing the proteome of mutant to wild-type cells. The relA gene mutation induced changes on key cellular processes, including the amino acids and nucleotide biosynthesis, the lipid metabolism, transport activities, transcription and translation processes and responses to stress. Furthermore, some of those changes were more pronounced under specific growth conditions, as the most significant differences in protein ratios were observed at one of the dilution rates. An effect of the relA gene mutation in the acetate overflow was also observed, which confers interesting characteristics to this mutant strain that could be useful in the production of recombinant proteins. Overall, these results provide a valuable insight into the E. coli stringent response under defined steady-state conditions, suggesting that this stress response might influence multiple metabolic processes like the acetate overflow or the catabolite repression.